2021
DOI: 10.3233/thc-202382
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the efficacy and safety of alteplase and urokinase in the treatment of acute cerebral infarction

Abstract: BACKGROUND: Acute cerebral infarction (ACI) is a common cerebrovascular disease in clinical practice. OBJECTIVE: The present study aims to investigate the efficacy and safety of alteplase and urokinase in treating ACI. METHODS: A total of 96 patients with ACI, who were treated with alteplase and urokinase, were selected as the main subjects. Among these patients, 45 patients with ultra-early acute cerebral infarction, who received intravenous thrombolysis with RT-PA (alteplase), were included in the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The symptomatic ICH rates were similar among the three groups ( 5 ). Recently, several comparative studies on the efficacy and safety of alteplase and urokinase for treating acute ischemic stroke have been conducted ( 13 15 ). These studies all demonstrated that urokinase and alteplase have similar therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptomatic ICH rates were similar among the three groups ( 5 ). Recently, several comparative studies on the efficacy and safety of alteplase and urokinase for treating acute ischemic stroke have been conducted ( 13 15 ). These studies all demonstrated that urokinase and alteplase have similar therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al reported that the ICH risk of alteplase was lower than urokinase ( 14 ). Bao et al found that patients treated with urokinase had a lower frequency of bleeding ( 13 ). Wang et al reported that the rates of subcutaneous ecchymosis, gingival bleeding, and ICH were similar between urokinase and alteplase ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The screening process is summarized in Figure 1. Thirty RCTs 28–57 met our inclusion criteria. The main characteristics of the included studies are provided in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Within the day of alteplase therapy, therapy of aspirin and clopidogrel [2][3][4] is not allowed. Observation index: Record NIHSS score of two groups of acute cerebral infarction patients before and after treatment, as well as adverse reactions of patients during treatment [5][6][7] . Efficacy evaluation index: With a view on NIHSS score of acute cerebral infarction, clinical efficacy of this study is divided into three levels, namely, effective, ineffective and markedly effective [8][9][10][11] .…”
Section: Et Al: Alteplase In the Treatment Of Acute Cerebral Infarctionmentioning
confidence: 99%